Thermoelectric Viscoelastic Fluid with Fractional Integral and Derivative Heat Transfer (Advances in Applied Mathematics and Mechanics, 2018)
A new mathematical model of magnetohydrodynamic (MHD) theory hasbeen constructed in the context of a new consideration of heat conduction with a time-fractionalderivative of order 0